ANALYSIS OF COSO-BASED INTERNAL CONTROL SYSTEM OF UNCOLLECTIBLE RECEIVABLES (Case study PT. PLN ULP Rantepao) - Mince Batara; Yunita Daud; Dina Ramba (Universitas Kristen Indonesia Toraja, 2022)
. Implementation of adjustments in the payment system from postpaid to prepaid for PT. PLN ULP Rantepao with the objective of reducing bad debts, but the accounts receivable report demonstrates an increase in bad debts over the last 3 years. The goal of this research is to examine the internal control system for bad debts in accordance with COSO. The descriptive qualitative method was used in this research. Using a random sampling technique, interviews, documentation, and observation were conducted. The sample used in this research is saturated. The significance of this research stems from the fact that bad debts have a significant impact on the company's financial health performance. (1) Changes to the prepayment system have no effect on the reduction in bad debts, according to the research results. (2) The internal control system at PT. PLN ULP Rantepao has not been properly implemented in terms of the 5 COSO components. Instances in which the risk assessment, control environment, and monitoring activities have been implemented, but only a few of each COSO component's items have been implemented. In the meantime, neither control activities nor information and communication have been properly implemented. (3) Control activity is relatively more influential in fostering the emergence of bad debts due to the low paying power and awareness of customers in meeting their obligations. This research will be more interesting if it is continued by investigating the failure factors of changing the prepaid payment system in an effort to reduce bad debts using a variety of research methods.